Offshore fishing vessel research vessel's repair and operation project - Ahmad Sabki, Ahmad Fuaad (Universiti Teknologi Malaysia, 1998)
The offshore fishing vessel design project was started in 1987 with the objective of developing the fishing industry particularly the offshore fishing industry. A research fund amounting to RM 1.55 million was obtained from IRPA for a project duration between 1987 until 1994 to start the data collection, design and the building of a working prototype. The repair project for the boat which involves an additional RM 230,000.00. This allocation was used to repair the damaged boat with a minor design modification. The repair process took almost 2 years and starts her operation as a fishing vessel in 2000 with additional allocation of RM 120,000.00 made available by the Research Management Center ( RMC ). Among the objectives of this phase of the research is to establish the effectiveness of the innovative technology available with TRF 1010. Data collection was organized for the operational data. Operations of TRF 1010 was initially centered in Kuala Terengganu with the crew mostly from the local fisherman and the operational method management was as practiced in that particular geographical area. Various management systems with change of crew set was introduced. During the final stages the boat operation was moved to Tok Bali with the use of Thai fisherman due to the acute shortage of local Malaysian fisherman. The offshore fishing industry is a very complex business structure. This complexity was discovered after several years of monitoring the operations of the fishing boat. Numerous factor contributes to the successful fishing venture. The fishing industry long term prospect does not seem to be favorable from a business point of view. This is primarily due to the basic fishing infrastructure is not well managed. Factors such as management system, human resource, fish sources, fishing technology, marketing, technology etc, is not integrated into focusing for the industry development. In general it can be concluded that the offshore fishing industry has enormous potential for further development if all the factors are synchronise and focused for the improvement of productivity. The factor of technology though important in the development, but other factors such as skillful fisherman, incentives and job status should be also given fair treatment in the future fishing industry.